2000
DOI: 10.1007/s004670050046
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in Saudi children with posterior urethral valves

Abstract: Posterior urethral valves (PUV) account for a sizeable proportion of children with chronic renal failure. Several criteria have been identified as predictive of future renal function in children with PUV. We compared the presenting features and initial treatment in two groups of Saudi children treated for PUV, with the aim of identifying any factors that might account for the differences observed in their renal function. One group (group A, 19 patients) had a serum creatinine of 80 micromol/l or less at follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
(16 reference statements)
1
13
0
1
Order By: Relevance
“…On the contrary, the present findings, as well as those of other investigators suggest no significant association between these variables and the subsequent renal function outcome. 4,5,10,18 Dissimilar study designs among these reports are probably the most likely cause for different results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…On the contrary, the present findings, as well as those of other investigators suggest no significant association between these variables and the subsequent renal function outcome. 4,5,10,18 Dissimilar study designs among these reports are probably the most likely cause for different results.…”
Section: Discussionmentioning
confidence: 89%
“…Long term prognosis varies from normal renal function to early onset ESRD. 5 This is a retrospective and non-randomized study with the aim to establish whether measurement of serum creatinine at presentation would predict the longterm renal outcome in children with PUV? The main finding was that initial serum creatinine level alone was the most significant correlate of follow-up renal function (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[44,45] Poor compliance is associated with the worst prognosis [46] but other factors implicated in the worsened prognosis in the boys include age at diagnosis, renal dysplasia, renal function before and after valve ablation, VUR, UTI, proteinuria, hypertension, and initial treatment. [42,43] The level of serum creatinine at 1 year old is shown to have a greater predictive value than the level at the time of diagnosis. [42] Because the levels of serum creatinine after relief of obstruction could refl ect more faithfully a kidney mass than those obtained before, and indeed, serum creatinine levels at 1 year old correlate strongly with the final outcome of patients.…”
Section: Long-term Prognosismentioning
confidence: 97%
“…A serum creatinine level of less than 8 mg/L at 1 year old is associated with normal renal function. [47,48] Recent studies [42,43] have shown that there is a clear prognostic relationship between the serum creatinine levels at 4-5 days after bladder catheterization and renal function.…”
Section: Long-term Prognosismentioning
confidence: 98%
See 1 more Smart Citation